Adsorption and sensing performances of transition metal (Pd, Pt, Ag and Au) doped MoTe2 monolayer upon NO2: A DFT study - Liu, Yun; Shi, Ting; Si, Quanlong; Liu, Tun (Physics letters. A, 2021)
•Pt, Pd, Ag and Au-doping behaviors on MoTe2 monolayer is expounded.•Adsorption performance of TM-MoTe2 monolayer to NO2 is fully analyzed.•DCD and EDD are considered to understand the charge-transfer behavior.•DOS, BS and FMO are used to understand the electronic behavior and sensing mechanism. Using density functional theory (DFT), the Pd, Pt, Ag and Au dopants are selected as the representatives to study the transition metal (TM)-doping behavior on the pristine MoTe2 monolayer and related NO2 sensing behavior. It is found that Pd and Pt adatoms prefer to be trapped through the TMo site, while Ag and Au dopants prefer to the TH site. The NO2 molecule behaves as electron-acceptor withdrawing charges from the TM-MoTe2 monolayer, based on the Hirshfeld analysis, and NO2 adsorption causes p-doping for Pd- and Pt-doped MoTe2 monolayer, and causes n-doping for Ag- and Au-doped MoTe2 monolayer, which decreases the bandgaps in the former two systems and increase the bandgaps in the latter two systems. Our calculations not only give an insight into the physicochemical property of TM-MoTe2 monolayer, but also elucidate their promising potential as novel NO2 sensors.